2002
DOI: 10.1002/nml.12406
|View full text |Cite
|
Sign up to set email alerts
|

Board Accountability: Lessons from the Field

Abstract: A CCOUNTABILITY has become a major issue throughout the nonprofit sector. Numerous approaches to strengthening performance in this area exist, and many nonprofit boards expect their executives to account for use of their organizations' resources. However, few boards apply any such expectations to themselves. As a result, they send inconsistent messages to their staff, consumer, sponsors, and the public. Finding ways to strengthen board performance in this area is crucial to the health of every nonprofit organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 15 publications
3
38
0
Order By: Relevance
“…Brown (2002) also demonstrates the link between processes and practices underpinning diversity efforts in a survey of sixty-two nonprofit organizations and case studies of two nonprofits with different governance strategies, where "highly inclusive organizations would use systematic recruitment practices" (p. 379). Holland (2002) also demonstrates the link among innovative work processes, the use of formal performance evaluation tools, and increased board accountability in nonprofits. Explicit employment contracts provide certainty, if not job security: shortterm or temporary work arrangements need not be precarious work arrangements.…”
Section: Human Resource Management Practicesmentioning
confidence: 95%
“…Brown (2002) also demonstrates the link between processes and practices underpinning diversity efforts in a survey of sixty-two nonprofit organizations and case studies of two nonprofits with different governance strategies, where "highly inclusive organizations would use systematic recruitment practices" (p. 379). Holland (2002) also demonstrates the link among innovative work processes, the use of formal performance evaluation tools, and increased board accountability in nonprofits. Explicit employment contracts provide certainty, if not job security: shortterm or temporary work arrangements need not be precarious work arrangements.…”
Section: Human Resource Management Practicesmentioning
confidence: 95%
“…Umbrella organizations tend to enforce a set of standards for resource management and board involvement (Holland, 2002), so it may be possible that relationships among the study' s variables were unique to organizations governed by a national organization. To determine if national affiliation moderated observed effects, we split the data set into two independent groups (national affiliation, n ϭ 12; no national affiliation, n ϭ 30) and estimated correlation coefficients among the study' s variables in each group.…”
Section: Hodge Piccolomentioning
confidence: 99%
“…The markets served by for-and nonprofit agencies tend to overlap (Rojas, 2000), and like their for-profit counterparts, limited resources and increased competition in service provision have forced nonprofit organizations to improve efficiency without compromising effectiveness (Callen, Klein, and Tinkelman, 2003;Speckbacher, 2003). Nonprofit agencies now face high expectations for service and accountability and must rely increasingly on active board members to support their mission (Carver, 1997;Holland, 2002).…”
mentioning
confidence: 97%
“…Research studies have shown that guideline on how to deal with conflict of interests can ameliorate the work of the board (Holland 2002)…”
Section: Dealing With Conflicts Of Interestmentioning
confidence: 99%